The foliar epidermal studies in some hitherto unstudied Euphorbiaceae - D. A. Patil2, H. A. Thakur1, (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-ansi-language: EN-US; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The paper is aimed at revealing various cellular structures, contours of foliar epidermis and foliar stomata of hitherto unstudied 17 species belonging 17 genera of the euphorbiaceous taxa. This information will be useful to reach sound taxonomic and phylogenetic deductions. Epidermal peels removed by TAT method or using Wellcol or Favicol were stained by safranin and fast green combination making semi permanent slides then camera lucida drawings provided to enlightened their structures.Ã‚Â Anomocytic stomatal type is predominant, while other types such as paracytic, hexacytic and anisocytic are also noted on the same foliar surface in different combinations. In majority of taxa, the leaves are hypostomatic, while in few they are amphistomatic. Distribution of stomata, stomatal index, stomatal frequency, stomatal size and other cell wall contours are described in detail in present study.